Acute effects of water temperature in swimming performance: a biophysical analysis - Gay, A.; Abraldes, J. A.; Zacca, R.; Morales, E.; López-Contreras, G.; Fernandes, R. J.; Arellano, R. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The aim of the present study was to explore the acute biophysical effects of different water temperatures in swimming. Ten male swimmers (28.20 ± 13.15 years old) completed two front crawl time-trials in a flume (24h rest in-between) at 18 and 26° C water temperature, both without wetsuit. The speed was common at both conditions and established according to a 400 m pre-test in a 25 m swimming pool (1.28 ± 0.13 m/s). The peak oxygen uptake (V.O2peak) maximal heart rate (HRmax), blood lactate concentrations ([La-]), energy cost (C), metabolic power (E. ) and total energy expenditure Etot were assessed. Stroke rate (SR), stroke length (SL), stroke index (SI), propelling efficiency (Eta p) and the Borg rating of perceived exertion scale (RPE) were calculated. Pair Student`s t-test was computed to compare both conditions. Time endured and (V.O2peak) were similar for 18 and 26° C conditions (313.44 ± 40.10 vs 282.27 ± 58.61s; mean difference: 31.16s; 95% CI: -32.12 to 94.45s; p=0.294; 47.54 ± 7.93 vs 51.91 ± 12.49 mL/kg/min mean difference: -4.37 mL/kg/min; 95% CI: -10.10 to 1.37s; p=0.119). However, lower [La-]peak (7.46 ± 3.33 vs 11.40 ± 1.58 mmol/L; p=0.002; Cohen's d: -1.42), RPE (5.10 ± 1.91 vs 7.10 ± 1.29; p=0.001; Cohen's d: -1.60) and .E values (1.23 ± 0.17 vs 1.41 ± 0.24; p=0.016; Cohen's d: -0.94) were observed at 18° C. The aerobic contribution (Aer) was higher (86.20 vs 81.90%; p=0.037; Cohen's d: 0.77) and anaerobic lactic (AnL) influence lower (5.80 vs 9.82%; p=0.001; Cohen's d: -1.46) when swimming at 18° C, but Etot (383 ± 60 vs 397 ± 98Kj) and C (0.96 ± 0.15 vs 0.99 ± 0.25kJ/m) remained similar within conditions. Furthermore, swimming at 18 and 26° C was not different from a general kinematical point of view (SR: 0.54 ± 0.04 vs 0.55 ± 0.06Hz; p=0.115; Cohen's d: -0.55; SL: 2.39 ± 0.20 vs 2.32 ± 0.20m; p=0.176; Cohen's d: 0.46; SI: 3.06 ± 0.53 vs 2.96 ± 0.44m2 s-1; p=0.145; Cohen's d: 0.50 and Eta p: 47 ± 4.7 vs 48 ± 6.4%; p=0.325; Cohen's d: -0.33). The tendency for lower values at 18° C are not in agreement with the literature and could be affected by the reduction of the blood flow volume in cold water and also due to methodological issues, particularly the learning effect regarding the use of the flume and breathing apparatus.